Estimating the Length of Right-Turn and U-Turn Pocket Lane Using Binomial Distribution - Chuwutthayakon, Chakrit; Noiruean, Tana; Boongrapue, Noppakun (RMUTL Engineering Journal, 2025)
Delays at U-turns and signalized intersections often occur due to insufficient right turns and U-turn pockets. It is significant to assess and determine the lengths of the pocket lane for right turns and U-turns to improve vehicle efficiency in the area. The right-turn and U-turn pocket designs are based on a binomial distribution and comply with the standards of the DOH of Thailand. Research demonstrates that the flow becomes congested and optimized of right-turn and U-turn pockets, which vary with the volume of turning vehicles. Once the lane does not lack the capacity of a pocket lane, the flow rate of vehicles in both directions decreases, but the flow for right turns and U-turns increases. Therefore, determining the appropriate turn pocket can boost the flow rate and reduce travel delays in those areas.